Pancreatic cancer stem cells in patient pancreatic xenografts are sensitive to drozitumab, an agonistic antibody against DR5. Issue 1 (21st June 2016) - Eng, Jason W.-L.; Mace, Thomas A.; Sharma, Rohit; Twum, Danielle Y. F.; Peng, Peng; Gibbs, John F.; Pitoniak, Rosemarie; Reed, Chelsey B.; Abrams, Scott I.; Repasky, Elizabeth A.; Hylander, Bonnie L.
Abstract : Background: Therapeutic resistance and tumor recurrence are two major hurdles in the treatment of pancreatic ductal adenocarcinoma. Recent findings suggest that both of these attributes are associated with a small subset of pancreatic tumor initiating cancer stem cells (CSCs). Here, we demonstrate that drozitumab, a human agonistic monoclonal antibody which binds the death receptor DR5, selectively eliminates CSCs, resulting in tumor growth inhibition and even regression of pancreatic tumors. Methods: To examine the efficacy of drozitumab against pancreatic CSCs, we treated patient-derived pancreatic tumor xenografts (PDX) in immunocompromised SCID mice and evaluated tumor control. To assess apoptosis following drozitumab treatment, we identified the CSCs as CD24+, CD44+, and EpCAM+ by FACS analysis, and measured in vivo and in vitro levels of cleaved caspase-3. Lastly, in vitro evaluation of DR5 re-expression was performed using isolated patient pancreatic cancer xenograft cells along with the cell line, Panc-1. After treatment with drozitumab, the remaining DR5- cells were assessed by FACS analysis for DR5 expression at the cell surface at 8, 24 and 48 h post-treatment. All in vivo growth data was analyzed by 2-way Anova, incidence data was analyzed using Mantel-Cox, and in vitro studies statistics were performed with a t-test. Results: We find that while 75–100 % of CSCs express DR5, only 25 % of bulk tumor cells express the death receptors at any one time. Consequently, drozitumab treatment of SCID mice bearing PDX kills higher percentages of CSCs than bulk tumor cells. Additionally, SCID mice implanted with isolated CSCs and then immediately treated with drozitumab fail to ever develop tumors. In vitro studies demonstrate that while drozitumab treatment reduces the DR5+ cell population, the remaining tumor cells begin to express DR5, suggesting a mechanism by which continuous administration of drozitumab can ultimately result in tumor regression despite the initially low percentage of DR5+ cells. Conclusions: Overall, our work reveals that treatment of pancreatic tumors with the drozitumab can lead to long-term tumor control by targeting both bulk cells and CSCs.